1905 Minn. Gen. Laws 162-63 - (:unkn) unknown (My University, 1905)
An Act Amending General Statutes of 1894, § 6445, Relating to Manslaughter, ch. 125, § 1: By shooting another with a gun, or other firearm when resulting from carelessness in mistaking the person shot for a deer or other animal is manslaughter in the first degree
Keywords: COMMITTING CRIME W/ WEAPON